2015
DOI: 10.1002/chem.201502536
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanoid/Alkali Metal β‐Triketonate Assemblies: A Robust Platform for Efficient NIR Emitters

Abstract: The reaction of hydrated lanthanoid chlorides with tribenzoylmethane and an alkali metal hydroxide consistently resulted in the crystallization of neutral tetranuclear assemblies with the general formula [Ln(Ae⋅HOEt)(L)4 ]2 (Ln=Eu(3+) , Er(3+) , Yb(3+) ; Ae=Na(+) , K(+) , Rb(+) ). Analysis of the crystal structures of these species revealed a coordination geometry that varied from a slightly distorted square antiprism to a slightly distorted triangular dodecahedron, with the specific geometrical shape being de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 57 publications
7
22
0
Order By: Relevance
“…Our initial results highlighted the serendipitous discovery of discrete bimetallic tetranuclear assemblies of formulation [Ln(Ae• HOEt)(tbm) 4 ] 2 , where Ae + is an alkali-metal cation and tbm − is the tribenzoylmethanide ligand. 29 Our studies have shown that this assembly is consistently obtained upon variation of the lanthanoid cation (Eu 3+ , Er + , and Yb 3+ ), alkali-metal cation (Na + , K + , or Rb + ), and alcoholic solvent (ethanol or n-butanol). Despite the structural novelty of these species, the most remarkable discovery occurred on investigating the photophysical properties of these lanthanoid assemblies.…”
Section: ■ Introductionmentioning
confidence: 58%
“…Our initial results highlighted the serendipitous discovery of discrete bimetallic tetranuclear assemblies of formulation [Ln(Ae• HOEt)(tbm) 4 ] 2 , where Ae + is an alkali-metal cation and tbm − is the tribenzoylmethanide ligand. 29 Our studies have shown that this assembly is consistently obtained upon variation of the lanthanoid cation (Eu 3+ , Er + , and Yb 3+ ), alkali-metal cation (Na + , K + , or Rb + ), and alcoholic solvent (ethanol or n-butanol). Despite the structural novelty of these species, the most remarkable discovery occurred on investigating the photophysical properties of these lanthanoid assemblies.…”
Section: ■ Introductionmentioning
confidence: 58%
“…This tendency agrees with the reported decreasing of luminescence intensity in [Ln(M · EtOH)(β‐tridiketonate) 4 ], when the geometry of [LnO 8 ] core has changed from TDD‐8 (for M = Cs, Rb) to SAPR‐8 (for M = Na). [7a] Authors attributed the luminescence quenching in [Ln(Na · EtOH)(β‐triketonate) 4 ] to the closer proximity of the solvent ethanol molecule coordinated with alkali metal ion to the Ln center. [7a] In our case, alkali metal coligands (H 2 O, MeOH) cannot have such effect because lanthanide ion is well shielded by both trifluoromethyl and branched dialkoxy substituents of diketonate anions.…”
Section: Resultsmentioning
confidence: 99%
“…[7a] Authors attributed the luminescence quenching in [Ln(Na · EtOH)(β‐triketonate) 4 ] to the closer proximity of the solvent ethanol molecule coordinated with alkali metal ion to the Ln center. [7a] In our case, alkali metal coligands (H 2 O, MeOH) cannot have such effect because lanthanide ion is well shielded by both trifluoromethyl and branched dialkoxy substituents of diketonate anions. Comparison of the photophysical properties of complex 4 and [(TbL 3 )(LiL)(H 2 O)][11b] supports this argument (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Research in this area has expanded to b-triketonates in an effort to boost the NIR efficiency of Er 3þ and Yb 3þ complexes. [22][23][24] This has been effective in boosting the NIR emissive output, an outcome justified as stemming from the removal of methylene C-H oscillators in close proximity to the Ln centre. [22] Furthermore, these complexes exhibit very long luminescent lifetimes relative to that of their b-diketonate counterparts.…”
Section: Introductionmentioning
confidence: 99%